Screening of Ten Tomato Varieties Processing Waste for Bioactive Components and Their Related Antioxidant and Antimicrobial Activities - Katalin Szabo; Zorița Diaconeasa; Adriana-Florinela Cătoi; Dan Cristian Vodnar (Antioxidants, 2019)
Global tomato production is currently around 180 million tons, of which more than a quarter undergoes processing. The removed peels, seeds, and vascular tissues usually end up in landfills, creating environmental pollution. In order to highlight the alternative use of these vegetal wastes, our study investigated 10 tomato varieties in terms of carotenoids content, phenolic composition, and their related antioxidant and antimicrobial activities. Tomato peels extracts were screened by high performance liquid chromatography with diode-array detection (HPLC/DAD) for qualitative and quantitative analyses. The extracts were tested against six bacterial strains to determine their antimicrobial effect; the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay was applied to estimate their antioxidant capacity. Total carotenoids content was significantly higher in Ţărănești roz, a local variety (5.31 ± 0.12 mg/100 g DW), while Mirsini, a commercial hybrid, presented significantly higher total phenolic content (155 ± 2 mg/100 g DW) compared to the mean value of all analyzed samples. The methanolic extracts of tomato peels presented acceptable antimicrobial activity against Staphilococcus aureus and Bacillus subtilis, and the mean antioxidant activity was 201 ± 44 µmol Trolox/100 g DW tomato peels. Considering that tomato peels have lycopene, β-carotene, lutein, and different phenolic compounds in their composition, tomato industrial by-products could represent a source of natural bioactive molecules with applicability in nutraceuticals and food industry.